BRAIN MECHANISMS FOR SOCIAL PERCEPTION: LESSONS FROM AUTISM AND TYPICAL DEVELOPMENT - PELPHREY, KEVIN A. (2008)
In this review, we summarize our research program that has as its goal charting the typical and atypical development of the social brain in children, adolescents, and adults with and without autism. We highlight recent work using virtual-reality stimuli, eye tracking, and functional magnetic resonance imaging that has implicated the superior temporal sulcus (STS) region as an important component of the network of brain regions that supports various aspects of social cognition and social perception. Our work in typically developing adults has led to the conclusion that the STS region is involved in social perception via its role in the visual analysis of others’ actions and intentions from biological-motion cues. Our work in adolescents and adults with high-functioning autism has implicated the STS region as a mechanism underlying social perception dysfunction in this neurodevelopmental disorder. We also report novel findings from a study of biological-motion perception in young children with and without autism.